(untitled) (Comillas Journal of International Relations, 2015)
The changes experienced by the international system after the Cold War entailed a transformation of the security concept, including aspects such as the referent object, the nature of values to be protected or the nature of security challenges. That change in the security concept meant an important broadening of it as long as issues which previously did not make part of the security agenda became included through a process of “securitization”. However, there are authors who consider that that process might allow the elites to increase their power dangerously. Consequently, they will advocate for a process of “desecuritisation”.